WOMEN POLICE IN CONTEMPORARY CHINA gender and policing. - Shen, Anqi. ([S.l.] : ROUTLEDGE, 2021)
This is the first book to look at women in policing in the mainland of the People's Republic of China. Informed by empirical data as well as rich secondary information drawn from a wide range of published materials, and written by a former police officer in China, this book offers a detailed discussion of key issues concerning women in the Chinese police. Mainly drawing on face-to-face interviews with police officers and student probationers in multiple force areas, Women Police in Contemporary China offers rich insights into women's lives in Chinese policing. The book first discusses how Chinese women were introduced to the male-only organisation and their representation in the Chinese police today. It elaborates women's experiences as female officers in the police and, more specifically, their everyday work, contributions to policing, women police's own perceptions of their roles and positions in the police profession and the gendered challenges and concerns facing them. It also looks at police occupational culture from a gendered lens. This book is illuminating reading for all those engaged in policing studies, gender and justice, policymaking, comparative criminal justice and all those interested in a woman's role in the Chinese police.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Gender Studies; Policewomen -- China